Clinical analysis of the effectiveness of the linear stapling apparatus for open and endovideosurgical surgeries - A. A. Supilnikov; S. A. Simatov; V. Y. Vartanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
On the basis of clinical experience of making anastomoses by apparatus and manual methods the comparative analysis of complications in the form of anastomosis failure during operations on the colon in cancer patients performed by both open and video endoscopic methods was carried out.